Net-Map: Collecting social network data and facilitating network learning through participatory influence network mapping - Schiffer, E.; Hauck, J. (SAGE Publications, 2010)
The authors describe how to use Net-Map,1 a low-tech, low-cost, interview-based mapping tool that can be used by researchers, facilitators, and implementers to (1) visualize implicit knowledge and understand the interplay of complex formal and informal networks, power relations, and actors’ goals; (2) uncover sources of conflicts as well as potentials for cooperation; (3) facilitate knowledge exchange and learning processes; and (4) develop visions and strategies to achieve common goals. The authors show that the tool can produce both qualitative and quantitative data to increase network understanding by going beyond the purely structure-driven approach of social network analysis (SNA) and combine structural measures with measures of attributes of actors, especially concerning their perceived influence and their goals. The authors present experiences from a field study from Ghana to illustrate the procedure and briefly discuss possible applications of the tool.